If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3m + 9m = 10(11 + 3m) + -9(6 + 2m) Combine like terms: 3m + 9m = 12m 12m = 10(11 + 3m) + -9(6 + 2m) 12m = (11 * 10 + 3m * 10) + -9(6 + 2m) 12m = (110 + 30m) + -9(6 + 2m) 12m = 110 + 30m + (6 * -9 + 2m * -9) 12m = 110 + 30m + (-54 + -18m) Reorder the terms: 12m = 110 + -54 + 30m + -18m Combine like terms: 110 + -54 = 56 12m = 56 + 30m + -18m Combine like terms: 30m + -18m = 12m 12m = 56 + 12m Add '-12m' to each side of the equation. 12m + -12m = 56 + 12m + -12m Combine like terms: 12m + -12m = 0 0 = 56 + 12m + -12m Combine like terms: 12m + -12m = 0 0 = 56 + 0 0 = 56 Solving 0 = 56 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 5x-32=15x-88 | | 7(y-3)=4y-39 | | 2c+6/-2=18 | | 3x+5+4x-35=180 | | 2x-5=4x-11 | | (n+4)*7=66 | | 7x^2+46x=21 | | 2(x+2)+3(x+4)=39 | | 0.2x-3=.01x+5 | | (n-9)*6=54 | | 20+8x= | | z+2z^2=15 | | 2x-9/6 | | 1/6(18b-12)=4b-9 | | 2(4c-1)-3=5c+7 | | 2x+79= | | 4-2+(6-8)= | | 7x-3=10x-4 | | 5-2p=-7 | | 5k^2-10k-75=0 | | 5(x-2)-3(x-5)=29 | | 9c+26=5c+6d-5 | | 3(3n^3+2n)-1=0 | | 930=-4x+967 | | x/3-2=29 | | -4(u+5)=-6u-32 | | x/3-2=27 | | -4*10+967= | | y=1-1 | | -4*7+967= | | 9i=x^4 | | -4*4+967= |